Understanding Teacher-Student Partnership For Islamic Educational Purpose: A Phenomenological Qualitative Study In An Islamic Boarding School - Rahmat Dipuro; Edy Purwanto; Saukani Nur Akbar; Ahsan Hakim (Education Research Center, 2026)
This study seeks to explore the meaning of teacher–student partnerships in achieving the goals of Islamic education within the context of a pesantren. Employing a qualitative approach grounded in transcendental phenomenology, this research focuses on uncovering the lived experiences of both teachers and students. Data were gathered through in-depth interviews, participant observation, and documentation involving twelve purposively selected participants. The analysis followed the phenomenological procedures proposed by Moustakas (1994), including epoche (bracketing), horizontalization, clustering of meaning, and the synthesis of textural and structural descriptions. The findings indicate that teacher–student partnerships in pesantren settings are understood through three interconnected dimensions. First, the partnership is experienced as a form of spiritual companionship rooted in adab (ethical conduct) and exemplified through role modeling. Second, it functions as a transformative interaction that shapes students’ character through continuous habituation. Third, it operates within a broader moral ecosystem sustained by the cultural and institutional practices of the pesantren. Overall, this study concludes that teacher–student relationships in Islamic education are inherently holistic, extending beyond instructional functions to become a foundational element in character formation.